Damage evolution of thermal shock in granite for enhanced geothermal systems - Liuke Huang; Guolin Rong; Xingchuan Liao; Nailing Xiu; Haifeng Fu; Dingwei Weng; Ling Yu (Geothermics, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Color-tunable and multi-stimuli-responsive room temperature phosphorescence based on an efficient supramolecular approach - Huan Yao; Yu-Ling Hu; Jun-Fu Chen; Han-Yu Luo; Wen-Jie Chen; Liu-Pan Yang; Li-Li Wang (Chemical Engineering Journal, 2026)

Pyridoxine and valproic acid co-exposure induces ER-mediated calcium dysregulation and cardiac toxicity in zebrafish - Wei-Hsiang Chen; Po-Yuan Chen; Wen-Yu Chung; Tein-Yu Chiu; Wei-Ling Lin; Chen-Yu Huang; Hui-Hua Chang; Chin-Wei Huang; Bing-Hung Chen; Lin Kang; Tzu-Fun Fu (Chemico-Biological Interactions, 2026)

Synergistic engineering of oxygen vacancies and AuCu interface on ZnO for enhanced photocatalytic biomass valorization - Hao-Yu Chen; Wu-Dan Yang; Jie-Yang Dong; Ling-Bao Wu; Dan-Dan She; Ze-Kuan Zhang; Tian-Jun Gong; Qi Zhang; Yao Fu (Chemical Engineering Journal, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

Experimental and numerical investigation on the shear mechanical behaviors and failure mechanisms of silty mudstone under seepage-stress coupling - Xiaowei Yu; Jiade Zhang; Hongyuan Fu; Ling Zeng; Hongri Zhang; Jingcheng Chen; Jie Liu (Bulletin of Engineering Geology and the Environment, 2026)

Molecular mechanisms underlying the maintenance of protein homeostasis in pearl gentian grouper under acute high-temperature stress - Qiu-Ting Yang; Ren-Xie Wu; Yan-Shan Liang; Ben-Ben Miao; Su-Fang Niu; Feng-Ling Lei; Fan-Li Long; Zhen-Bang Liang; Yu-Xin Shen; Yu Fu (Journal of Thermal Biology, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Evaluation and comparison of TCR repertoire differences between patients with cervical cancer and healthy individuals - Wenwen Gao; Cong Wang; Jiawen Jia; Yiqian Li; Ting Li; Ling Liu; Yi Zhang; Haibin Yu; Cuiping Yang; Xiaoli Fu; Yongbin Chen; Yan Cheng (Science China Life Sciences, 2026)

Effects of personality and body weight on foraging behavior and vigilance: a case study in a small rodent - Yu-Chuang Hui; Shu-Jing Gao; Xuan-Wen Li; Wei-Qi Chen; Yue-Yue Yang; Xue-Dong Bai; Qin Su; Fu-Shun Zhang; Li-Qing Wang; Ling-Ying Shuai (Behavioral Ecology and Sociobiology, 2026)

Non-uniform gradient depressurization strategy for balancing heat transfer and gas production in Dual-Gas Co-Production systems - Xian Sun; Hang Zheng; Hui Yang; Fu-Jun Cheng; Zhen Pan; Wen-Chen Han; Hao-Xiang Sun; Yang Yu; Ling-Ban Wang; Chang-Yu Sun (Fuel, 2026)

Species-specific accumulation and biomagnification of PFASs in aquatic and terrestrial organisms from the Xisha Islands - Yu-Quan Zhang; Jun Xiang; Jiao-feng Gu; Peng Zeng; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Li-cheng Wang; Hang Zhou; Ling Mo (Marine Pollution Bulletin, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Fixation of atmospheric nitrogen on present-day Mars during dust events - Wenshuo Mao; Xiaohui Fu; Zhongchen Wu; Jiang Zhang; Zongcheng Ling; Yang Liu; Yu-Yan Sara Zhao; Jiacheng Liu; He Cui; Hitesh G. Changela; Yuheng Ni; Lifang Li; et al. (Earth and Planetary Science Letters, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Nor-halimane and spiro-labdane diterpenoids with anti-inflammatory activity from Leucas ciliata Benth - Jia-Cai Kuang; Fu-Ling Cen; Xuan Zhang; Xu-Hua Nong; Xue-Ming Zhou; Xiao-Bao Li; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2026)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Efficient tanshinone metabolic engineering in Salvia miltiorrhiza through modified multiplex CRISPR/Cas9 system - Han Zheng; Qi Yao; Qi Liu; Badalahu Tai; Yi Ye; Ling Li; Yaojie Zhang; Yuyang Zhao; Xiaokai Gao; Shuai Liu; Xueqing Fu; Muyao Yu; et al. (Chemical Engineering Journal, 2025)

Macrophage and keratinocyte cell assays suggest that the supercritical CO2 extract of black soybean possesses anti-inflammatory and skin barrier-protective effects - Ying Wu; Jia-Ying Wu; Jing-Xuan Bai; Xiao-Qi Wang; Amy Sze-Man Li; Xiao-Yun Fan; Rui-Xuan Han; Li Wang; Xiaobing Dou; Xiu-Qiong Fu; Zhi-Ling Yu (Food Research International, 2025)

Evaluating the ecological and agricultural benefits of intelligent sustainable green energy floating gardens: impacts on microorganisms and vegetable growth - Yuan-Hsiou Chang; Hsiao-ling Lu; Tsai-Fu Chuang; Hong-Bin Lai; Yi-Zhen Yu (Environmental Science and Pollution Research, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Pressure makes diamonds: Enhanced permeation resistance to petroleum hydrocarbons of a novel in-situ mixed wall material - Zhe-Yuan Jiang; Xian-Lei Fu; Yu-Ling Yang; Wei-Yi Xia; Min Wang; Heng Zhuang; Zi-Han Lu; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Role of macrophage ATP metabolism disorder in SiO2‑induced pulmonary fibrosis: a review - Hui-jie Hu; Yuan-yuan Fu; Shu-ling Du; Yu-han Zhang; Zhao-qiang Zhang; Gui-zhi Han (Purinergic Signalling, 2025)

Selective salt separation and resource recovery via nanofiltration in coal-to-ethylene glycol wastewater - Zheng-Jun Fu; Bo-Zhi Chen; Kai Yu; Jian-Guo Hu; Pengli Chen; Hui-Qin Zhang; Mei-Ling Liu; Shi-Peng Sun (Journal of Water Process Engineering, 2025)

Enhanced cathodic performance for simultaneous removal of Cr (VI) and norfloxacin: The synergistic effect and electron transfer triggered by high-entropy spinel oxide - Yu-Xin Guo; De-Wang Wei; Shang-Mei Fu; Ling-Zhen Miao; Lu Ying; Lei Wu; Jie Zhu (Journal of Environmental Chemical Engineering, 2025)

The nuclear receptor gene SfE75 regulates the molting of Sogatella furcifera - Yi-Ming Wang; Yan-Yu Wang; Ming-Fu Gong; Shi-Yan Zhang; Jiang-Ling Chen; Xin Li; Cao Zhou; Hong Yang (Journal of Asia-Pacific Entomology, 2025)

Species-specific bioaccumulation and biotransformation of two novel brominated flame retardants in fish: Insights from isotope fractionation - Ling Mo; Guang-Yu Liao; Bin Tang; Cheng-Zhong Fu; Dong-Jing Zhou; Dong-Wei Du; Wei-Keng Luo; Rong-Fa Xu; Ming-Zhong Ren; Jing Zheng (Environmental Research, 2025)

Microplastics in groundwater: Environmental fate and possible interactions with coexisting contaminants - Shengfeng Liu; Chengcheng Li; Jochen Bundschuh; Xubo Gao; Xing Gong; Huihui Li; Mengyun Zhu; Ling Yi; Wenxuan Fu; Fengze Yu (Environmental Pollution, 2025)

Accurately estimating and revealing the patterns of leaf C:N:P stoichiometry with remote sensing and neural network methods in a karst area - Wen He; Yuefeng Yao; Yanqiong Li; Ling Yu; Longkang Ni; Bolin Fu; Jinjun Huang; Donxing Li (Computers and Electronics in Agriculture, 2025)

Karst water quality, source of pollution, and health risk assessment in China - Gongzhe Peng; Xubo Gao; Aqsa Naseem; Yunfei Zhang; Xiangjie Wang; Wenxuan Fu; Fengze Yu; Siyuan Ma; Wanpeng Shi; Ling Yi; Chengcheng Li; Wei Liu; et al. (Science of The Total Environment, 2025)

Numerical study of deformation inhomogeneity and its effect on mechanical properties of the heavy-wall offshore pipeline fabricated by different processes - Ling-zhi Xu; Gui-ying Qiao; Ying-long Ma; Yu Gu; Kai Xu; Xiao-wei Chen; Fu-ren Xiao (Ocean Engineering, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

Activation of 5-HT6 Receptors in the Ventrolateral Orbital Cortex Produces Anti-Anxiodepressive Effects in a Rat Model of Neuropathic Pain - Yu-Long Zhao; Hui-Yuan Yi; Sani Sa’idu Baba; Yi-Xiao Guo; Xiao-Cui Yuan; Xue-Mei Hou; Ling-Li Liang; Fu-Quan Huo (Molecular Neurobiology, 2025)

Recent progress of piezoelectric materials applied in photocatalytic CO2 reduction: A review - Yi-fu Liu; Rui-tang Guo; Sheng-hui Guo; Ling-qi Yu; Ji-song Yan; Wei-guo Pan (Journal of Environmental Chemical Engineering, 2024)

Insights into novel phosphorus-doped biochar for tetracycline removal: Non-radical oxidation and adsorption - Xi Fu; Xiaojun Niu; Dongqing Zhang; Ling Li; Xingyao Ye; Shan Liao; Maoyu Li; Chuting Lao; Deye Chen; Yu Lin; Zhiquan Yang (Journal of Environmental Chemical Engineering, 2024)

Real-time monitoring of activated sludge flocs via enhanced mask region-based Convolutional Neural networks - Tie-Fu Xu; Cai-Ling He; Guo-Tao Wang; Bo-Wen Li; Yu Tao (Environmental Research, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

High efficiency removal of antibiotic resistance gene with designer zinc-finger protein - Jianghao Yu; Meng Fang; Lulu Shi; Jiaming Zhu; Chengzhang Fu; Youming Zhang; Hai Xu; Ling Li; Yu Shen; Mingyu Wang (Bioresource Technology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Experimental investigation of the matching boundary and optimization strategy of a variable geometry turbocharged direct-injected hydrogen engine - Feng-yu Lai; Bai-gang Sun; Zhi-fu Zhang; Shi-wei Zhang; Kang-da Wang; Xue-ming Ju; Qing-he Luo; Ling-zhi Bao; Felix Leach (Fuel, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

The crosslinking sites and molecular conformation of gelatin hydrogel modified by transglutaminase - Yunke Yang; Ling Mao; Hai Chen; Liang Ma; Yu Fu; Yuhao Zhang (Food Hydrocolloids, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The phosphate-solubilising fungi in sustainable agriculture: unleashing the potential of fungal biofertilisers for plant growth - Shih-Feng Fu; Vignesh Kumar Balasubramanian; Chih-Ling Chen; Thuy Trang Tran; Jothi Basu Muthuramalingam; Jui-Yu Chou (Folia Microbiologica, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Structurally diverse isoquinoline alkaloids from the barks of Alangium salviifolium (L. f.) Wangerin and their cytotoxicity - Yan-Mei Wei; Xuan Zhang; Fu-Ling Cen; Yi-Yi Du; Yuan-Ling Liu; Qiao-Yuan Han; Zhang-Xin Yu; Guang-Ying Chen (Phytochemistry, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Sulfation, characterization, antibacterial activity, and action mechanism of rice bran polysaccharides - Bing-Jie Chen; Yong-Jin Qiao; Gang Yu; Xiao Wang; Yi Zhang; Ling-Lin Fu (Food Bioscience, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Damage constitutive model for soft rocks and its experimental verification on silty mudstone considering cyclic rock‒water interactions - Xiao-Wei Yu; Hong-Yuan Fu; Ling Zeng; Jie Liu; Xing-Yu Qiu (Bulletin of Engineering Geology and the Environment, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Cactodera guizhouensis n. sp. (Nematoda: Heteroderinae), a new species of cyst-forming nematode parasitizing potato in Guizhou, China - Chun-Hui Ni; Yu-Jia Xie; Si-Hua Yang; Zai-Fu Yang; Chun-Ling Xu; Hui Xie (European Journal of Plant Pathology, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Electrospinning-assisted construction of rapid proton conduction channels in halloysite nanotube-encapsulated ionic liquid-embedded sulfonated poly(ether ether ketone) proton exchange membranes - Chunyong Xiong; Zhiwei Ling; Bei Wang; Yang Yu; Qingting Liu; Xudong Fu; Chonggang Wu; Rong Zhang; Shengfei Hu; Xujin Bao; Jun Yang (Fuel, 2024)

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Hedscandines A-C, three undescribed indole alkaloids from Hedyotis scandens with their anti-MRSA activity - Yu-Jun Wang; Xue Chen; Yong Yin; Wei Zhou; Pei-Fu Zhou; Ling-Gao Zeng; Chang-Hua Hu; Guo-Ping Yin (Phytochemistry, 2024)

Enhancement of ester biosynthesis in blueberry wines through co-fermentation via cell–cell contact between Torulaspora delbrueckii and Saccharomyces cerevisiae - Yu Wang; Yu Fu; Qi Zhang; Yue Zhu; Qin Yang; Chen Bian; Lu-Lu Zhao; Qi Chen; Hai-Jun Bi; Xiao-Hui Yang; Xue-Ling Gao (Food Research International, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

Human Bone Marrow Derived-Mesenchymal Stem Cells Treatment for Autoimmune Premature Ovarian Insufficiency - Wen-Qing Ma; Ai-Ping Zhuo; Yuan-Ling Xiao; Meng Gao; Yu-Tao Yang; Li-Chao Tang; Yan-Hong Wu; Dan Tian; Xia-Fei Fu (Stem Cell Reviews and Reports, 2024)

Hydrogen sulfide promoted cell differentiation, antioxidant ability, and flavonoids accumulation in Ginkgo biloba L. suspension cells - Jin-ling Lu; Yu-chen Hu; Ying Chen; Rui Liu; Jing-jing Di; Ting-ting Feng; Fu-liang Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Deriving fine-scale patterns of sea surface temperature in coral reef habitats using the Landsat 8 thermal infrared sensor - Xiu-Ling Zuo; Ke-Fu Yu; Bin-Ni Qin; Xiao-Peng Duan; Zuo-Fang Yao; Fen-Zhen Su (Frontiers in Marine Science, 2023)
The available sea surface temperature (SST) products are too coarse to assess the fine-scale (<1 km) SST variations related to coral bleaching. In this study, we proposed an optimal SST inversion model using Landsat 8 thermal infrared sensor (TIRS) images to derive fine-scale SST patterns in the coral reef habitats of the Xisha Islands, South China Sea. Our study included two parts: 1) six SST inversion models were developed using the radiative transfer method and the split window (SW) algorithm in the hot season and cool season, from which the optimal SST inversion model was determined; and 2) the optimal model was applied to 47 Landsat 8 TIRS images to derive the SST spatial and temporal pattern among the geomorphic zones of six reefs in hot and cool season conditions. Compared with the measured sea temperature data and the verified MODIS SST products, the SST6 model using the SW algorithm was optimal, with an RMSE of approximately 0.64°C in the hot season. The average SST results usually had a pattern of reef flat > lagoon > reef slope/offshore sea. The reef flat was usually approximately 0.05°C–0.2°C hotter than the lagoon in the hot season. The SST in the lagoon also increased from south to north and the shallow lagoon was usually warmer than the deep lagoon in the hot season. Our results suggested that scleractinian corals in the reef flat and the lagoon were more susceptible to bleaching-level thermal stress than other geomorphic zones. During the cool season, the SST fluctuated markedly among coral reefs and geomorphic zones.

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

Experimental study on unloading failure characteristics and damage evolution rules of deep diorite based on triaxial acoustic emission tests - Yang Li; Jianxin Fu; Nai Hao; Weidong Song; Ling Yu (Geosciences Journal, 2023)

SWD1 epigenetically chords fungal morphogenesis, aflatoxin biosynthesis, metabolism, and virulence of Aspergillus flavus - Xiaohua Pan; Ling Hao; Chi Yang; Hong Lin; Dandan Wu; Xuan Chen; Mengjuan Zhang; Dongmei Ma; Yu Wang; Wangzhuo Fu; Yanfang Yao; Shihua Wang; et al. (Journal of Hazardous Materials, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

Combined effects of light pollution and vegetation height on behavior and body weight in a nocturnal rodent - Ling-Ying Shuai; Li-Qing Wang; Yang Xia; Jin-Yu Xia; Kang Hong; Ya-Nan Wu; Xin-Yi Tian; Fu-Shun Zhang (Environmental Pollution, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Effects of Torulaspora delbrueckii co-fermented with Saccharomyces cerevisiae on physicochemical and aromatic profiles of blueberry fermented beverage - Yu Wang; Xiao-Yan Qi; Yu Fu; Qi Zhang; Xiao-Han Wang; Meng-Yao Cui; Ying-Ying Ma; Xue-Ling Gao (Food Chemistry, 2023)

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Transcriptional regulatory network of high-value active ingredients in medicinal plants - Han Zheng; Xueqing Fu; Jin Shao; Yueli Tang; Muyao Yu; Ling Li; Luqi Huang; Kexuan Tang (Trends in Plant Science, 2023)

Spinal MCP-1 Contributes to Central Post-stroke Pain by Inducing Central Sensitization in Rats - Fei Yang; Jun-Jie Jing; Si-Yin Fu; Xiu-Zhu Su; Yu-Ling Zhong; Dong-Sheng Chen; Xiao-Zhi Wu; Yi-Qing Zou (Molecular Neurobiology, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Geochemical characteristics of shales from Upper Carboniferous Yanghugou formation in Weiningbeishan area, China: Implication for provenance, source weathering and tectonic setting - Yu Ma; Hongze Yang; Yanyun Ma; Yongping Wang; Wenzhong Wu; Na An; Shuofeng Tian; Ling Ma; Deliang Fu (Marine and Petroleum Geology, 2023)

Monitoring of tree tilt motion using lorawan-based wireless tree sensing system (IoTT) during super typhoon Mangkhut - Wai Yi Chau; Yu-Hsing Wang; Siu Wai Chiu; Pin Siang Tan; Mei Ling Leung; Hoi Lun Lui; Jimmy Wu; Yun Man Lau; Kuan-Fu Liu; Billy Chi Hang Hau (Agricultural and Forest Meteorology, 2023)

Efficient enrichment of iodine by supported ionic liquid with three effective adsorption sites: Heteroatoms, fused aromatic rings and ionic bond - Yu-Qin Xiang; Yuan-Hao Wang; Hao Chen; Jie Fu; Qiu-Hong Zhu; Xiao-Lan Yang; Xin-Hong Xu; Song Qin; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Derivation of new resistance principle on flow-induced morphological response of flexible vegetation - Feng-Cong Jia; Wei-Jie Wang; Ling-Hua Liu; Jin-Jin Li; Ai-Ping Huang; Jing Zhang; Yi-Cheng Fu; Yang Yu (Environmental Science and Pollution Research, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Enhanced Fluoride Stabilization by Modified Layered Double Hydroxides for the Remediation of Soil Pollution: Performance and Mechanism - Dong-ling Wang; Yu-han Fu; Jin-yan Yang (Water, Air, & Soil Pollution, 2022)

Application of regional citrate anticoagulation in patients at high risk of bleeding during intermittent hemodialysis: a prospective multicenter randomized controlled trial - Xiaoyan Tang; Dezheng Chen; Ling Zhang; Ping Fu; Yanxia Chen; Zhou Xiao; Xiangcheng Xiao; Weisheng Peng; Li Cheng; Yanmin Zhang; Hongbo Li; Kehui Li; et al. (Journal of Zhejiang University-SCIENCE B, 2022)

Spatiotemporal Variations of Microwave Land Surface Emissivity (MLSE) over China Derived from Four-Year Recalibrated Fengyun 3B MWRI Data - Rui Li; Jiheng Hu; Shengli Wu; Peng Zhang; Husi Letu; Yu Wang; Xuewen Wang; Yuyun Fu; Renjun Zhou; Ling Sun (Advances in Atmospheric Sciences, 2022)

Rapid triage for ischemic stroke: a machine learning-driven approach in the context of predictive, preventive and personalised medicine - Yulu Zheng; Zheng Guo; Yanbo Zhang; Jianjing Shang; Leilei Yu; Ping Fu; Yizhi Liu; Xingang Li; Hao Wang; Ling Ren; Wei Zhang; Haifeng Hou; et al. (EPMA Journal, 2022)
Background Recognising the early signs of ischemic stroke (IS) in emergency settings has been challenging. Machine learning (ML), a robust tool for predictive, preventive and personalised medicine (PPPM/3PM), presents a possible solution for this issue and produces accurate predictions for real-time data processing. Methods This investigation evaluated 4999 IS patients among a total of 10,476 adults included in the initial dataset, and 1076 IS subjects among 3935 participants in the external validation dataset. Six ML-based models for the prediction of IS were trained on the initial dataset of 10,476 participants (split participants into a training set [80%] and an internal validation set [20%]). Selected clinical laboratory features routinely assessed at admission were used to inform the models. Model performance was mainly evaluated by the area under the receiver operating characteristic (AUC) curve. Additional techniques—permutation feature importance (PFI), local interpretable model-agnostic explanations (LIME), and SHapley Additive exPlanations (SHAP)—were applied for explaining the black-box ML models. Results Fifteen routine haematological and biochemical features were selected to establish ML-based models for the prediction of IS. The XGBoost-based model achieved the highest predictive performance, reaching AUCs of 0.91 (0.90–0.92) and 0.92 (0.91–0.93) in the internal and external datasets respectively. PFI globally revealed that demographic feature age, routine haematological parameters, haemoglobin and neutrophil count, and biochemical analytes total protein and high-density lipoprotein cholesterol were more influential on the model’s prediction. LIME and SHAP showed similar local feature attribution explanations. Conclusion In the context of PPPM/3PM, we used the selected predictors obtained from the results of common blood tests to develop and validate ML-based models for the diagnosis of IS. The XGBoost-based model offers the most accurate prediction. By incorporating the individualised patient profile, this prediction tool is simple and quick to administer. This is promising to support subjective decision making in resource-limited settings or primary care, thereby shortening the time window for the treatment, and improving outcomes after IS.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

Molecular identification and characterization of ‘Candidatus Phytoplasma asteris’-related strain associated with pepper (Capsicum annuum L.) yellow crinkle disease in China - Shao-shuai Yu; Qing-hua Tang; Deng-qiang Fu; Rui-ling Zhao; Wei-wei Song; Wei Yan; Wei-quan Qin (Journal of General Plant Pathology, 2021)

The contrasting relationships of relative humidity with influenza A and B in a humid subtropical region - Qian Wu; Jun He; Wen-Yan Zhang; Ke-Fu Zhao; Jing Jin; Jun-Ling Yu; Qing-Qing Chen; Sai Hou; Meng Zhu; Zhiwei Xu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Rhizosphere microbiome modulated effects of biochar on ryegrass 15N uptake and rhizodeposited 13C allocation in soil - Yingyi Fu; Amit Kumar; Lijun Chen; Yuji Jiang; Ning Ling; Runze Wang; Qiong Pan; Bhupinder Pal Singh; Marc Redmile-Gordon; Lu Luan; Qin Li; Quan Shi; et al. (Plant and Soil, 2021)

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Safety of protease inhibitors and Arbidol for SARS-CoV-2 pneumonia in Zhejiang Province, China - Yong-zheng Guo; Kai-jin Xu; Yong-tao Li; Jia-dan Fu; Min Xu; Ling Yu; Ji-fang Sheng; Biao Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

The effect of baicalin on microRNA expression profiles in porcine aortic vascular endothelial cells infected by Haemophilus parasuis - Shulin Fu; Jun Liu; Jianfeng Xu; Sanling Zuo; Yunfei Zhang; Ling Guo; Yinsheng Qiu; Chun Ye; Yu Liu; Zhongyuan Wu; Yongqing Hou; Chien-An Andy Hu (Molecular and Cellular Biochemistry, 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Genome-Wide Analysis of LAZ1 Gene Family from Maize - Bing Liang Liu; Hao Qiang Yu; Qian Wen; Feng Ling Fu; Wan Chen Li (Journal of Plant Growth Regulation, 2020)

Epidemiology and HBGA-susceptibility investigation of a G9P[8] rotavirus outbreak in a school in Lechang, China - Lun-Ai Guo; Meng Zhang; Yu-zhen Hou; Haitao Hu; Ling Fang; Ming Tan; Qiong Huang; Hui Li; Li-Mei Sun; Xi Jiang; Wen-Fang Tan; Shixing Tang; et al. (Archives of Virology, 2020)

Disease progression model of 4T1 metastatic breast cancer - Liang Yang; Ling Yong; Xiao Zhu; Yaoyao Feng; Yu Fu; Daming Kong; Wei Lu; Tian-yan Zhou (Journal of Pharmacokinetics and Pharmacodynamics, 2020)

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Potentiation effects by usnic acid in combination with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Rui-Chun Fu; Wei Yu; Yun-Ling Zhang; Gen-Chun Wang (Medicinal Chemistry Research, 2018)

Interaction network of core ABA signaling components in maize - Ying-Ge Wang; Feng-Ling Fu; Hao-Qiang Yu; Tao Hu; Yuan-Yuan Zhang; Yi Tao; Jian-Kang Zhu; Yang Zhao; Wan-Chen Li (Plant Molecular Biology, 2018)

Anti-complementary constituents of Anchusa italica - Yu-zhen Hou; Kui-kui Chen; Xi-ling Deng; Ze-long Fu; Dao-feng Chen; Qi Wang (Natural Product Research, 2017)

Testing of antiviral characteristics of flammutoxin in transgenic tobacco - Li-Ping Wu; Xue-Ling Gao; Yuan-Dan Duan; Ye-Yu Bian; Tao Yang; Ming-Jia Fu (Journal of Plant Diseases and Protection, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The anticancer and antiobesity effects of Mediterranean diet - Hiu Yee Kwan; Xiaojuan Chao; Tao Su; Xiuqiong Fu; Anfernee Kai Wing Tse; Wang fun Fong; Zhi-Ling Yu (Critical Reviews in Food Science and Nutrition, 2017)

The Regulatory Roles of ncRNA Rli60 in Adaptability of Listeria monocytogenes to Environmental Stress and Biofilm Formation - Ye-long Peng; Qing-ling Meng; Jun Qiao; Kun Xie; Cheng Chen; Tian-li Liu; Zheng-xiang Hu; Yu Ma; Xue-peng Cai; Chuang-fu Chen (Current Microbiology, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

CTRP3 attenuates post-infarct cardiac fibrosis by targeting Smad3 activation and inhibiting myofibroblast differentiation - Dan Wu; Hong Lei; Jin-Yu Wang; Cheng-Lin Zhang; Han Feng; Feng-Ying Fu; Li Li; Li-Ling Wu (Journal of Molecular Medicine, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Polyphenols in Regulation of Redox Signaling and Inflammation During Cardiovascular Diseases - Ling Niu; Xiu-hua He; Qing-wen Wang; Ming-yu Fu; Feng Xu; Ying Xue; Zhen-zhou Wang; Xin-jiang An (Cell Biochemistry and Biophysics, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Comparison of complete genome sequences of dog rabies viruses isolated from China and Mexico reveals key amino acid changes that may be associated with virus replication and virulence - Fulai Yu; Guoqing Zhang; Xiangfu Zhong; Na Han; Yunfeng Song; Ling Zhao; Min Cui; Simon Rayner; Zhen F. Fu (Archives of Virology, 2014)

MicroRNA-30c serves as an independent biochemical recurrence predictor and potential tumor suppressor for prostate cancer - Xiao-hui Ling; Zhao-dong Han; Dan Xia; Hui-chan He; Fu-neng Jiang; Zhuo-yuan Lin; Xin Fu; Ye-han Deng; Qi-shan Dai; Chao Cai; Jia-hong Chen; Yu-xiang Liang; et al. (Molecular Biology Reports, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

Organochlorine pesticides in the dust fall around Lake Chaohu, the fifth largest lake in China - Hui-Ling Ouyang; Qing-Mei Wang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Yu-Jiao Jiang; Chen Yang; Bin Yang; Fu-Liu Xu (Environmental Monitoring and Assessment, 2014)

Influence of Electromagnetic Signal of Antibiotics Excited by Low-Frequency Pulsed Electromagnetic Fields on Growth of Escherichia coli - Yin-Lung Ke; Fu-Yu Chang; Ming-Kun Chen; Shun-Lai Li; Ling-Sheng Jang (Cell Biochemistry and Biophysics, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Water–gas exchange of organochlorine pesticides at Lake Chaohu, a large Chinese lake - Hui-Ling Ouyang; Wei He; Ning Qin; Xiang-Zhen Kong; Wen-Xiu Liu; Qi-Shuang He; Chen Yang; Yu-Jiao Jiang; Qing-Mei Wang; Bin Yang; Fu-Liu Xu (Environmental Science and Pollution Research, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The monitoring results of electromagnetic radiation of 110-kV high-voltage lines in one urban location in Chongqing P.R. China - Qi-zhong Qin; Yu Chen; Ting-ting Fu; Li Ding; Ling-li Han; Jian-chao Li (Environmental Monitoring and Assessment, 2012)

CDH1 promoter polymorphism and stomach cancer susceptibility - Yi-Ling Li; Zhong Tian; Jian-Bing Zhang; Bao-Yu Fu (Molecular Biology Reports, 2012)

17beta-estradiol attenuates pressure overload-induced myocardial hypertrophy through regulating caveolin-3 protein in ovariectomized female rats - Yu-Hong Cui; Zhi Tan; Xiao-Dong Fu; Qiu-Ling Xiang; Jin-Wen Xu; Ting-Huai Wang (Molecular Biology Reports, 2011)

Inhibitory Effect of Delphinidin on Monocyte–Endothelial Cell Adhesion Induced by Oxidized Low-Density Lipoprotein via ROS/p38MAPK/NF-κB Pathway - Chun-ye Chen; Long Yi; Xin Jin; Ting Zhang; Yu-jie Fu; Jun-dong Zhu; Man-tian Mi; Qian-yong Zhang; Wen-hua Ling; Bin Yu (Cell Biochemistry and Biophysics, 2011)

Chemical composition and antioxidant activity of the essential oil of endemic Viola tianshanica - Jin Yang; Zhen Qu; Yu-Ling Xiao; Guo-Fu Qiu; Tao Zhang; Zhong-Yuan Wu; Xian-Ran He; Xian-Ming Hu (Natural Product Research, 2011)

Overexpression of survivin and cyclin D1 in CHO cells confers apoptosis resistance and enhances growth in serum-free suspension culture - Xinghui Zhao; Junwei Guo; Yingqun Yu; Shaoqiong Yi; Ting Yu; Ling Fu; Lihua Hou; Wei Chen (Biotechnology Letters, 2011)

A haplotype in the CCR5 gene promoter was associated with the susceptibility to HIV-1 infection in a northern Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Xueyuan Jia; Chao Shen; Yanling Zhao; Yan Jin; Yang Yu; Hong Ling; et al. (Molecular Biology Reports, 2011)

The Removal of Ocular Artifacts from EEG Signals Using Adaptive Filters Based on Ocular Source Components - Hsiao-Lung Chan; Yu-Tai Tsai; Ling-Fu Meng; Tony Wu (Annals of Biomedical Engineering, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Design and implementation of an adaptive code discriminator in a DSP/FPGA-based Galileo receiver - Jyh-Ching Juang; Yu-Hsuan Chen; Tsai-Ling Kao; Yung-Fu Tsai (GPS Solutions, 2010)

Arsenic-Induced QT Dispersion is Associated with Atherosclerotic Diseases and Predicts Long-Term Cardiovascular Mortality in Subjects with Previous Exposure to Arsenic: A 17-Year Follow-Up Study - Chih-Hao Wang; Chi-Ling Chen; Chuhsing Kate Hsiao; Fu-Tien Chiang; Ling-I Hsu; Hung-Yi Chiou; Yu-Mei Hsueh; Meei-Maan Wu; Chien-Jen Chen (Cardiovascular Toxicology, 2010)

CCR2-64I allele is associated with the progression of AIDS in a Han Chinese population - Lidan Xu; Yuandong Qiao; Xuelong Zhang; Haiming Sun; Jingwei Wang; Donglin Sun; Yan Jin; Yang Yu; Feng Chen; Jing Bai; Hong Ling; Kaili Wang; et al. (Molecular Biology Reports, 2010)

Prostasin inhibits cell invasion in human choriocarcinomal JEG-3 cells - Xiao-jie Ma; Ya-yuan Fu; Yu-xia Li; Li-mei Chen; Karl Chai; Yan-ling Wang (Histochemistry and Cell Biology, 2009)

Chronic fatigue of the small enterprise workers participating in an occupational health checkup center in southern Taiwan - Fu-Wei Wang; Yu-Wen Chiu; Ming-Shium Tu; Ming-Yueh Chou; Chao-Ling Wang; Hung-Yi Chuang (International Archives of Occupational and Environmental Health, 2009)

Effect of meal size on excess post-exercise oxygen consumption in fishes with different locomotive and digestive performance - Shi-Jian Fu; Ling-Qing Zeng; Xiu-Ming Li; Xu Pang; Zhen-Dong Cao; Jiang-Lan Peng; Yu-Xiang Wang (Journal of Comparative Physiology B, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Effects of moderate and severe intermittent hypoxia on vascular endothelial function and haemodynamic control in sedentary men - Jong-Shyan Wang; Liang-Yu Chen; Li-Lan Fu; Mei-Ling Chen; May-Kuen Wong (European Journal of Applied Physiology, 2007)

Expression of SWAP-70 in the uterus and feto-maternal interface during embryonic implantation and pregnancy in the rhesus monkey (Macaca mulatta) - Jing Liu; Ya-Yuan Fu; Xiao-Yang Sun; Fei-Xue Li; Yu-Xia Li; Yan-Ling Wang (Histochemistry and Cell Biology, 2006)

The receptor tyrosine kinase inhibitor SU11248 impedes endothelial cell migration, tubule formation, and blood vessel formation in vivo, but has little effect on existing tumor vessels - Katherine L. Osusky; Dennis E. Hallahan; Allie Fu; Fei Ye; Yu Shyr; Ling Geng (Angiogenesis, 2004)

The serotonergic system may be involved in the sleep-inducing action of oleamide in rats - Jing-Yu Yang; Chun-Fu Wu; Fang Wang; Hong-Rui Song; Wen-Jun Pan; Yu-Ling Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)